Different Neural Information Flows Affected by Activity Patterns for Action and Verb Generation - Wang, Zijian; Zhang, Zuo; Sun, Yaoru (Frontiers in Psychology, 2022)
Shared brain regions have been found for processing action and language, including the left inferior frontal gyrus (IFG), the premotor cortex (PMC) and the inferior parietal lobule (IPL). However, in the context of action and language generation that shares the same action semantics, it is unclear whether the activity patterns within the overlapping brain regions would be the same. The changes in effective connectivity affected by these activity patterns are also unclear. In this fMRI study, participants were asked to perform hand action and verb generation tasks toward object pictures. We identified shared and specific brain regions for the two tasks in the left PMC, IFG and IPL. The mean activation level and multi-voxel pattern analysis revealed that the activity patterns in the shared sub-regions were distinct for the two tasks. The dynamic causal modelling results demonstrated that the information flows for the two tasks were different across the shared sub-regions. These results provided the first neuroimaging evidence that the action and verb generation were task-context driven in the shared regions, and the distinct patterns of neural information flow across the PMC-IFG-IPL neural network were affected by the polymodal processing in the shared regions.